2017
DOI: 10.18632/oncotarget.15308
|View full text |Cite
|
Sign up to set email alerts
|

NRIP/DCAF6 stabilizes the androgen receptor protein by displacing DDB2 from the CUL4A-DDB1 E3 ligase complex in prostate cancer

Abstract: Both nuclear receptor interaction protein (NRIP) and DNA damage binding protein 2 (DDB2) belong to the Cullin 4 (CUL4)-DDB1 binding protein family and are androgen receptor (AR)-interacting proteins. Here, we investigated the expression patterns of the NRIP, DDB2 and AR proteins in human prostate cancer tissues and found that the expression levels of NRIP and AR were higher, but the DDB2 level was lower, in prostate cancer tissues than in non-neoplastic controls, suggesting NRIP as a candidate tumor promoter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Nuclear receptor interaction protein might participate in various cellular functions, including regulating muscle contraction, promoting cell growth, and inhibiting protein degradation . Here, we provide a novel function of NRIP and a novel muscle‐derived neuronal supporting factor indicating that muscular NRIP expression is essential for spinal motor neuron support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nuclear receptor interaction protein might participate in various cellular functions, including regulating muscle contraction, promoting cell growth, and inhibiting protein degradation . Here, we provide a novel function of NRIP and a novel muscle‐derived neuronal supporting factor indicating that muscular NRIP expression is essential for spinal motor neuron support.…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic variations in the NRIP genome location are associated with cardiovascular disease, osteoporosis, and schizophrenia . Nuclear receptor interaction protein is also named DCAF6 and belongs to Cul4‐DDB1 associated factors . Mutation at R317C of DCAF8 responding to DDB1 binding was identified as the genetic cause of axonal hereditary motor and sensory neuropathy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we reported that CRL4 DDB2 is a new E3 ubiquitin ligase targeting CDT2 for its proteolysis. DNA damage binding protein 2 (DDB2), another substrate receptor for CRL4 E3 ubiquitin ligase [18][19][20][21][22], is originally identi ed as damage-speci c DNA binding protein, and involves in the early step of DNA damage recognition of nucleotide excision repair (NER), which is induced by UV radiation [23][24][25][26][27]. Recently, increasing evidences suggest that DDB2 plays an important role in suppressing tumorigenesis [19,[28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing evidences suggest that DDB2 plays an important role in suppressing tumorigenesis [19,[28][29][30][31][32]. DDB2 is low expressed in skin cancer, breast cancer, colon cancer, prostate cancer, and ovarian cancer [18,29,30,[33][34][35]. DDB2-de cient mice have the high rate to develop malignant tumors compared to their XP-de cient littermates [36].…”
Section: Introductionmentioning
confidence: 99%